Fish neuroendocrinology - Bernier, Nicholas J. (Fish physiology, 2009)
The study of fish neuroendocrinology has had a significant impact on our general understanding of the functional roles and evolution of a variety of neurochemical messengers and systems. Not only do fish possess unique neuroendocrine features, they have also been and remain an important vertebrate models for the discovery of new neuropeptides. In the last fifty years, neuroendocrinologists have documented a complex and seemingly infinite number of interactions between hormones and nerve structures. Gradually emerging from this knowledge is an understanding of the specific neurohormonal pathways and the messengers responsible for maintaining homeostasis in an aquatic environment and for regulating the functional systems that allow for the highly diverse life histories and reproductive tactics of fish Despite its recent growth, breadth and unique attributes, there is no single text covering the discipline of fish neuroendocrinology. In fact, other than a few mammalian neuroendocrinology textbooks, there is a serious lack of texts in comparative neuroendocrinology. Currently, information on the anatomical organization and function of the various neuroendocrine systems in fish is only available in original research papers and reviews. By providing a current and comprehensive volume that highlights the specific properties of fish neuroendocrinology, this book will go beyond being the only reference text for fish neuroendocrinologists and will also serve comparative physiologists, endocrinologists, neuroanatomists and behaviourists interested in understanding the reciprocal actions between the nervous and endocrine systems.